ETHICAL DILEMMA OF OFFENSIVE MAGIC IN HARRY POTTER AND THE DEADLY HOLLOWS - Iftinan Rose Putri Safana (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
In Rowling’s Harry Potter and the Deathly Hallows, the employment of unforgivable curses and other offensive magic creates ethical dilemma in the context of combat and self-defense. This shows that there is a tension between ideal ethical principles and real needs in self-defense efforts which also often occurs in the real world where considerations often experience a dilemma between punishment and human rights. This study seeks to examine the moral judgment regarding the use of magic from the perspectives of Deontology and Utilitarianism, as well as its impact on the moral decisions of the main characters. This study employs qualitative methodologies and a textual analysis methodology to examine the theories of Deontology, which examines morality based on universal obligations and principles, and Utilitarianism, which assesses morality based on the impact and benefits for a large number of people. According to the findings, the Deontological perspective views Harry, Molly Weasley, Hermione, and Snape's usage of unforgivable curses and offensive magic as a moral deviance, regardless of the good intentions or advantages. Utilitarianism, on the other hand, defends these behaviors since they benefit the greater number of people. This ethical quandary highlights the conflict between the moral need to not injure others and the need to defend oneself in battle situations.